Semiotika Nonverbal dalam Musik Video “Azza” Karya Rhoma Irama (Kajian Semiotika Roland Barthes) - Anindita Fikri Amalia; Nurdien Harry Kristanto; Sukarjo Waluyo (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe non-verbal semiotics and its relation to Roland Barthes' semiotics, namely connotation and denotation. This research with the object of the study of the music video "Azza" by Rhoma Irama uses qualitative research methods to find non-verbal semiotics contained in the object of study. The results of this study, namely in the music video "Azza" by Rhoma Irama, there are seven body signs, namely (a) signals; (b) facial expressions; (c) eye contact; (d) body language; (e) touch; (f) cue; and (g) dance. It is also related to Roland Bathes' semiotics. Signs expressed in the music video have connotative and denotative meanings that the singer wants to convey through his music and videos. The connotative meaning in the music video "Azza", sung by Rhoma Irama, can be seen in the scenes glorifying God's power.